Avaliação da produção de biogás a partir da digestão anaeróbica : estudo de caso em uma fábrica de chocolate - Pereira, Flávio Raposo (2014)
The research aimed at evaluating the biogas production from the anaerobic digestion at the sewage treatment unit of a chocolate factory, which contemplates an ascending flow reactor of sludge blanket. The main focus was related to the emission assessment and the removal of organic load for the generation of biogas, favoring its conversion into electric and/or thermal energy. Due to the little variability of the oxygen chemical demand emission (COD) in the effluents and the good efficiency concerning the removal of this organic load (83%), the results obtained indicate that the reactor produces, in a continuing way, about 49.020 m³/year biogas, what is correspondent to 5,60 m³/h. The research evaluated two scenarios for the energetic use of this gas, contemplating the possibility to generate electricity by a motor-generator set or by the burn in the boilers combined with natural gas (NG) in order to produce steam. The first scenario took into consideration the production of electric energy through a motorgenerator system of 9,5 Kwh by biogas that when operating at 20 h/day is able to produce about 58.400 Kwh/year and obtain an income of R$ 20.296,00/year. In the second scenario, it was verified that the biogas generated during the anaerobic treatment is equivalent to 28.431 m³/year of NG. Considering that the actual NG consumption in the boilers is 2.756.938 Nm³/year, it is stated that the biogas use would represent a savings of 1,02 % of NG, in financial terms, it would correspond to approximately R$ 32.540/year to the company. This way, it is concluded that the use of biogas in the boiler brings a greater financial return with the savings of natural gas, comparing with the results for electricity production. The biogas produced in the treatment Station, through studies, brings benefits that cover the three pillars of Sustainable Development: the economic, the environmental and the social one. The matching of these three pillars becomes necessary in order to create an economic growth able to optimize and preserve the natural resources, without compromising the needs of the future generations.